EXPRESSION OF TIM-3 BY IMMUNE CELLS IN MICE WITH AN EXPERIMENTAL MODEL OF THE TUMOR PROCESS - Vialichka, Alesia; Nazaranka, Elizaveta; Lutskovich, Dmitry; Nizheharodava, Darya (Journal of the Belarusian State University. Ecology, 2026)
T-cell immunoglobulin and mucin domain-3 (TIM-3) is an inhibitory immune checkpoint that is expressed on immune and tumor cells. However, to date, the dual role of TIM-3 has been shown: on the one hand, the receptor acts as a negative regulator of antitumor immunity and is associated with a lower survival rate in cancer patients, and on the other hand, it may indicate a positive prognosis for certain types of cancer.The study was conducted on A/J mice with an experimental neuroblastoma model. The cellular composition of the secondary organs of the immune system and TIL (tumor-infiltrating lymphocytes), as well as the level of TIM-3 expression, were determined using flow cytometry and monoclonal antibodies. Statistical processing is performed in Statistica 8.0. The secondary lymphoid organs of the immune system (lymph nodes and spleen) were characterized by a predominant (more than 90%) content of lymphocytes, while the remaining cells were identified as granulocytes and monocytes/macrophages in all the studied groups. At the same time, the content of tumor-associated macrophages (TAM) increased statistically significantly in the TIL population of mice in the experimental group. In mice with an experimental neuroblastoma model, a decrease in CD3+ T-lymphocytes in the lymph nodes and spleen was found relative to the comparison group (p=0.01) in combination with an increase in CD3+CD4-CD8-T-cells in the lymph nodes (p=0.01). In the experimental group, there was a statistically significant increase in TIM-3 on CD3+T-lymphocytes, mainly on CD3+CD8+T-cells. An inverse relationship was found between the level of TIM-3 expression on CD3+CD8+T-lymphocytes and the amount of TAM (R=-0.70; p=0.02) in lymph nodes, as well as the correlation of TIM-3 expression on CD3+ T-lymphocytes of the spleen and TAM content in mice with neuroblastoma (R=0.90; p=0.001), which may be a potential mechanism of pathological immune tolerance in the formation of the oncological process.
Keywords: tumor microenvironment; neoplasm; immune cells; experimental model; immune checkpoints; T-cell immunoglobulin and mucin domain-3